The significance of Eurasian and European integrations in the foreign policy of the Republic of Belarus (1991–2017) - Tsikhamirau, Aliaksandr V. (Journal of the Belarusian State University. International Relations, 2018)
The article analyzes the position of the Republic of Belarus on the issue of participation in the processes of Eurasian and European integrations in 1991–2017. It is noted that the integration policy of Belarus was built on the basis of preserving the sovereignty of the Belarusian state, equality of the participants of the integration projects and real benefits for the Belarusian state and the Belarusian people. To a greater extent, the Eurasian integration projects met these requirements (BelarusianRussian enterprises, EurAsEC, EAEU), which predetermined the active participation of Belarus in Eurasian integration. The European integration project did not meet the expectations of the Belarusian authorities and did not receive massive support from the Belarusian society. As a consequence, the cooperation with the EU became a subsidiary direction of the Belarusian foreign policy and integration activity.
Keywords: Republic of Belarus; integration; Union State of Belarus and Russia; Eastern Partnership; the Eurasian Economic Union; the European Union